Controllable Band Alignment Transition in InSe–MoS2 Van der Waals Heterostructure (Phys. Status Solidi RRL 7/2018). Issue 7 (5th July 2018) - Chen, Xi; Lin, Zheng‐Zhe; Ju, Ming
Abstract : Two‐dimensional materials, which lead to drastic reduction in the characteristic lengths of electronic devices, have been considered as building blocks for future nanoelectronics and optoelectronics. Different two‐dimensional materials can be reassembled into layered heterostructures, i.e. van der Waals heterostructures. Van der Waals heterojunctions with type‐II band alignment, in which electrons and holes are separated in distinct layers and thus the recombination is avoided, play a central role in optoelectronic devices. In article no.1800102, Zheng‐Zhe Lin and co‐workers propose a type‐ I→II band alignment transition in InSe–MoS2 van der Waals heterostructure that can be controlled by changing interlayer distance or applying perpendicular external electric field. Changing band offset into type II facilitates the possible use and flexible band engineering of van der Waals heterostructure in optoelectronics. The results provide a guidance in improving the properties of van der Waals heterostructures.